2007
DOI: 10.1007/s11224-007-9233-3
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity of Rees-type hydrocarbons—a DFT computational study

Abstract: The structure and aromatic properties of Rees hydrocarbons 7bH-cyclopent [cd]indene and its benzoannelated derivative 1a and 2a, respectively, are examined by the B3LYP/6-31+G(d) calculations employing HOMA criterion of Krygowski and coworkers. It is shown that 1a possesses strong p-electron delocalization over the perimeter of the CC bonds, thus forming a quasi-[10]annulene pattern. Its aromatic character is determined to be 83%. In contrast, 2a is less convenient model system for [14]annulene. The reason beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Recently, we have demonstrated that Rees compound I is a quasi-[10]annulene, since it possesses strong π-electron delocalization over the CC perimeter. Its aromatic character was determined to be 83% employing the geometric HOMA (harmonic oscillator model of aromaticity) criterion, proposed by Krygowski and co-workers .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have demonstrated that Rees compound I is a quasi-[10]annulene, since it possesses strong π-electron delocalization over the CC perimeter. Its aromatic character was determined to be 83% employing the geometric HOMA (harmonic oscillator model of aromaticity) criterion, proposed by Krygowski and co-workers .…”
Section: Resultsmentioning
confidence: 99%
“…[23] For the nonplanar molecule 7bH-cyclopent-[cd]indene, a HOMA value of 0.83 was found. [16] The lower HOMA values correspond to compounds with a nonplanar benzene ring. A trend of increasing ΔP values with decreasing HOMA is observed ( Figure 2); however, a decrease in aromaticity is not always paralleled by a distortion of the benzene plane.…”
Section: Resultsmentioning
confidence: 99%
“…The HOMA parameters were applied to the study of aromaticity of nonplanar molecules. [16,17] The relationship between these factors in sterically crowded aromatic compounds with NH···O intramolecular hydrogen bonds is the object of this study. As model compounds, we chose substituted 2,4,6-trinitroanilines (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Vianello and Maksić [389] studied the structure and aromatic properties of the Rees-type hydrocarbons, 7bH-cyclopent[cd]indene and its benzoannelated derivatives. Such species include ''fluoradene'' [390,391] for which no enthalpy of formation has been reported in the experimental literature, a surprising omission given its exceptional acidity [392,393].…”
Section: Issuementioning
confidence: 99%